Cost engineering as an innovative tool for economic stabilization and financial diagnostics of construction participants in the conditions of a changing environment of development projects of post-war reconstruction - Kovtun , Anton; Bielienkova , Olha; Shevchuk , Кyrylo; Dubinin , Denis (Ways to Improve Construction Efficiency, 2025)
The article substantiates the feasibility of using cost engineering as an innovative management tool for economic stabilization and financial diagnostics of construction participants in the conditions of a changing environment of the implementation of development projects of post-war reconstruction. The relevance of the study is due to the increasing level of uncertainty, risks and resource constraints in the construction sector, which requires a transition from traditional approaches to cost management to complex methodologies focused on achieving value, financial stability and adaptability of development subjects.The study summarizes scientific approaches to the interpretation of economic security, financial stability and financial diagnostics of construction enterprises, and also analyzes the evolution of cost engineering from a tool for local cost reduction to an integrated mechanism for value management at all stages of the project life cycle. Particular attention is paid to the role of financial modeling, investment analysis, budgeting, life cycle analysis and cash flow management in the cost engineering system. It is proven that the combination of functional-cost analysis with financial and risk-oriented tools allows not only to optimize the cost structure, but also to carry out financial diagnostics of construction participants, timely identify threats to their economic stability and form sound management decisions. It is substantiated that in post-war reconstruction projects, cost engineering acquires special importance as a tool for ensuring the transparency of financial flows, rational use of investment and public resources, and achieving a balance between economic efficiency, quality, and social feasibility of project solutions.The practical significance of the results obtained lies in the possibility of using the proposed approaches by public administration bodies, development companies, investors, and contracting organizations in planning and implementing construction projects in post-crisis and post-war conditions. The scientific novelty of the study lies in the justification of cost engineering as an integration tool for economic stabilization and financial diagnostics, adapted to the conditions of high turbulence in the development environment.